Neonatal Gardner Fibroma Leads to Detection of Familial Adenomatous Polyposis: Two Case Reports - Mattias Schäfer; Martina Kadmon; Wolfgang Schmidt; Irmgard Treiber; Ute Moog; Christian Sutter; Maximilian Stehr (Georg Thieme Verlag KG, 2016)
Abstract Gardner fibromas (GFs) have only recently been described as poorly circumscribed tumor-like lesions, which are exceedingly rare in children. GFs are associated with APC gene mutations and therefore with familial adenomatous polyposis (FAP). So far there is only very limited literature on GF in the neonatal period. We present two children with GF diagnosed at birth and subsequent FAP with very different clinical courses. In one case, the disease led to extensive surgery of the thoracic wall and detection of FAP in the father with the need of immediate proctocolectomy. In the other patient (with a positive family history for FAP) the disease remained stable. Our cases indicate that the diagnosis of GF in the neonatal period requires the exclusion of FAP both in the child as well as the parents. Since the clinical behavior of GF cannot be predicted, continuous monitoring is mandatory. Depending on tumor site and growth, individual therapeutic options must be thoroughly considered. Surgical resection, if necessary, has to be inevitably total to prevent recurrence.